2022
DOI: 10.1016/j.eclinm.2022.101277
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury in precariously housed persons: Incidence and risks

Abstract: Background Homeless and precarious housed persons are particularly prone to traumatic brain injuries (TBIs), but existent incidence rates are hampered by poor case acquisition. We rigorously documented TBIs in precariously housed persons transitioning in and out of homelessness. MethodsBetween December 2016 and May 2018, 326 precariously housed participants enrolled in a longitudinal study in Vancouver, Canada were assessed monthly for TBI occurrences after education on sequelae. Over one participant-year, 243… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…56 Moreover, a substantial proportion of our study population had a history of residency in the DTES, where over 50% of residents were reported to have experienced at least one TBI event per year. 57 Our results also confirm that this subgroup of PLWH is significantly more likely to have TBI and experience a more significant number of TBI episodes. Previous studies have also identified a substantially higher risk of TBI in similar marginalised settings with higher rates of homelessness, substance use and crime.…”
Section: Bmj Public Healthsupporting
confidence: 80%
See 1 more Smart Citation
“…56 Moreover, a substantial proportion of our study population had a history of residency in the DTES, where over 50% of residents were reported to have experienced at least one TBI event per year. 57 Our results also confirm that this subgroup of PLWH is significantly more likely to have TBI and experience a more significant number of TBI episodes. Previous studies have also identified a substantially higher risk of TBI in similar marginalised settings with higher rates of homelessness, substance use and crime.…”
Section: Bmj Public Healthsupporting
confidence: 80%
“…59 TBI among marginalised individuals frequently results from falls, physical assaults and hitting one's head on objects, often in the presence of substance intoxication. 57 Since TBI is associated with dementia and other adverse health outcomes, targeted interventions such as enhancement of neighbourhood safety and effective SUD treatment are required to prevent TBIs among PLWH, especially those in marginalised neighbourhoods. Moreover, understanding the clinical and epidemiological features of dementia in relation to TBI and SUD is critical in designing preventative measures to reduce the individual and societal impacts of these conditions in our population.…”
Section: Bmj Public Healthmentioning
confidence: 99%
“…Anxiety was reported as a reason for medical cannabis use in 40 patients (75.5%). Anxiety is commonly reported as a reason for initiating medical cannabis use [44,48,73]. Mental health issues following a TBI are common [74] and medical cannabis might help to alleviate these symptoms.…”
Section: Mental Healthmentioning
confidence: 99%
“…The interrelationships between GBV and SI contribute to catastrophic health and social inequities for women, for instance, poverty, homelessness, isolation, depression, posttraumatic stress disorder, traumatic brain injury, and premature death ( Boyd et al, 2018 ; Hayashi et al, 2016 ; O'Connor et al, 2022 ; Stubbs et al, 2022 ; Wallstam et al, 2017 ). Despite these pressing problems, women encounter considerable challenges in receiving appropriate and timely health and social care ( Bungay, 2013 ; Kneck et al, 2021 ; Maulsby et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%